Perancangan Sistem Pengarsipan Surat Masuk dan Surat Keluar pada Desa Kampung Besar Menggunakan Metode Alphabetical Filing dan Chronology System - Noer Azni Septiani; Deden Haitami (Universitas Batanghari Jambi, 2020)
The archive is one source of information that has an important function to support the process of administration and management of an agency. All activities carried out by the agency, whether in the form of proposals, correspondence or other documents will be archived. The recorded information is evidence and documentation or memory for the agency concerned. In the village of Kampung Besar Teluknaga the letter filing system that is running is still not computerized, so that in the system there are some problems in the accuracy of the data. This study aims to create a letter management system to improve the efficiency of retrieval in the context of investigative and official reference activities. The Alphabetical Filing and Chronology System method is used in system design because it is simple and easy to implement, archiving letters to large villages in the bay using a desktop program that is easy to use in the system is also easy in terms of use and maintenance. In addition to simplifying the process of archiving letters, the system also facilitates employees in the process of making reports and searching data. The proposed system is expected to improve the current system so that it can make the filing system of incoming and outgoing letters in the village of Kampung Besar Teluknaga more effective and efficient.